Common stem origin of left gastric, right and left inferior phrenic arteries, in association with a hepatosplenomesenteric trunk, independently arising from the abdominal aorta: Case report using MDCT angiography. Issue 8 (17th December 2012) - Matusz, Petru; Loukas, Marios; Iacob, Nicoleta; Ples, Horia
<x xml:space="preserve">Abstract</x> We describe in this paper a rare case of a 45‐year‐old male with a common stem origin of the left gastric artery (LGA), right inferior phrenic artery (RIPA), and left inferior phrenic artery (LIPA), in association with the presence of a hepatosplenomesenteric trunk (HSMT) arising from the abdominal aorta (AA), as revealed by routine multidetector computed tomography (MDCT) angiography. The common stem origin of the LGA, RIPA, and LIPA had an endoluminal diameter of 3.3 mm, the LGA of 2.8 mm. The endoluminal diameter of the RIPA and LIPA was at the origin of approximately 1 mm, complicating selective chemoembolization of the liver parenchyma. Clin. Anat. 26:980–983, 2013. © 2012 Wiley Periodicals, Inc.